Genetic Diversity of Plasmodium falciparum Glutamate Rich Protein in Patients Attending the Merauke Hospital in Papua Province, Indonesia - Thomas Tandi Manu; Puspa Wardhani; Heny Arwati; Aryati Aryati (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2021)
Malaria remains an important health problem in Indonesia with the highest transmission in Papua Province, an eastern part of this country. The genetic diversity of malaria parasites is the main problem in understanding several aspects of malaria infections and the dynamics of their transmission, which also play a role in the development of a vaccine. Plasmodium falciparum is the deadliest of the human malaria parasites. Plasmodium falciparum glutamate-rich protein (Pfglurp) is one of the many erythrocytic stages antigens currently under development for a vaccine. The Pfglurp gene hasbeen extensively used as a marker to investigate the genetic diversity, Multiplicity of Infection (MOI), the level of malaria transmission, immunity against malaria, as well as a discriminatory instrument to distinguish new from recrudescent infections of the field parasite population. Thus, this genotyping study aimed to find out the genetic population of P.falciparum at the Merauke District, Province of Papua, Indonesia. DNA samples were isolated from Dried Blood Spots (DBS) obtained from P.falciparum infected patients in the Regional Public Hospital of Merauke, Province of Papua, Indonesiaduring May 2019-July 2019. The isolated DNAs were then amplified for nested Polymerase Chain Reaction (PCR) prior to Pfglurp genotyping. The glurp gene was identified in all 51 DBS samples of P.falciparum-infected patients, and 18 variants of allele were found. Among them, 45.10% were found to bear multigenotype infections. The size of the dominant allele (12.5%) was 701-750 bp. The MOI was 1.58. The genetic population of P.falciparum in Merauke Hospital has contained a higher percentage of multigenotypes compared with monogenotypes indicating the high transmission of malaria in the studied area.